Effectiveness of Contour Augmentation with Guided Bone Regeneration: 10-Year Results. (March 2018) - Chappuis, V.; Rahman, L.; Buser, R.; Janner, S.F.M.; Belser, U.C.; Buser, D.
In aesthetic sites, the integrity of the facial bone wall dimension in the anterior maxilla is jeopardized by physiologic and structural changes postextraction. An effective regenerative protocol is key to reestablish and maintain the hard and soft tissue dimensions over time. The present prospective case series study examined the effectiveness of early implant placement with simultaneous contour augmentation through guided bone regeneration with a 2-layer composite graft in postextraction single-tooth sites over an observation period of 10 y among 20 patients. The median peri-implant bone loss was 0.35 mm between the 1- and 10-y examination. A success rate of 95% was obtained, with pleasing aesthetic outcomes and a high median Pink Esthetic Score (8). Implant crowns (ICs) revealed significant median facial recession between IC10y and IC1y (0.17 mm). The facial bone wall dimensions were assessed by preoperative cone beam computed tomography and 2 subsequent scans taken at 6 and 10 y. The median facial bone wall thickness increased significantly from 0 mm at surgery to 1.67 mm at the 10-y examination. The facial vertical bone wall peak (DIC) was located at a median distance of 0.16 mm coronal to the implant shoulder. The facial vertical bone loss of DIC amounted to 0.02 mm between 6 and 10 y. Equivalence testing was performed for the null hypothesis of a difference of >0.2 mm per year between 2 respective time points, showing stable bone conditions. Modulating factors influencing the regenerative outcomes at 10 y were the preoperative proximal crest width and soft tissue thickness. In conclusion, the present study confirmed the long-term effectiveness of early implant placement with simultaneous contour augmentation through guided bone regeneration with a 2-layer composite graft in postextraction single-tooth sites offering stable bone conditions with low risks of mucosal recessions over an observation period of 10 y (ClinicalTrials.gov NCT03252106).